Factors Determine Students’ Perception On Cash Waqf Awareness in Malaysia - Dzuljastri bin Abdul Razak; Mohamed Noordeen Mohamed Imtiyaz; Ariji Naji; Hamadah Azzam; Fatimah Hassan; Ainul Syahidah (Journal of Islamic Management Studies, 2022)
The contribution of cash waqf, which had traditionally only been engaged in the empowerment of vacant land, has now become more varied and covering different areas of community welfare, such as health, education and business development. Although the purpose of the cash waqf program is very strong, the presence of cash waqf and the waqf institution themselves are still not well known in the community, especially in educational field. As a result, the cash waqf program remained stagnant in achieving the goals of the Maqashid Syariah. Thus, the purpose of this paper is therefore to find out the factors that determine the students' perceptions of the cash waqf awareness in Malaysia, based on its acceptance, practice and expectations. The survey method was provided to 342 respondents which were students from a university in Malaysia, International Islamic University Malaysia (IIUM). By conducting multiple linear regression and factor analysis to examine the relationship between variables, the result shows that the stronger of the dependent variables, the more it affects students ' perception on the cash waqf awareness in Malaysia.